2014
DOI: 10.1177/1933719113519172
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Detection of Surface Abnormalities: A Comparison of 2- and 3-Dimensional Ultrasound and 3-Dimensional Virtual Reality Ultrasound

Abstract: The aim was to determine the diagnostic performance of 3-dimensional virtual reality ultrasound (3D_VR_US) and conventional 2-and 3-dimensional ultrasound (2D/3D_US) for first-trimester detection of structural abnormalities. Forty-eight first trimester cases (gold standard available, 22 normal, 26 abnormal) were evaluated offline using both techniques by 5 experienced, blinded sonographers. In each case, we analyzed whether each organ category was correctly indicated as normal or abnormal and whether the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One previous study has shown a high sensitivity for the detection of structural anomalies in the first trimester using 3D VR and a trend towards improved detection rates [ 16 ]. 3D VR may especially improve the detection of surface anomalies in the first trimester [ 20 ]. Timely detection of major congenital malformations will provide women at risk with additional time to perform (genetic) testing as well as more time to consider continuation or termination of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous study has shown a high sensitivity for the detection of structural anomalies in the first trimester using 3D VR and a trend towards improved detection rates [ 16 ]. 3D VR may especially improve the detection of surface anomalies in the first trimester [ 20 ]. Timely detection of major congenital malformations will provide women at risk with additional time to perform (genetic) testing as well as more time to consider continuation or termination of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, the detection rate in a high risk population is estimated at 61%, and in a low risk population at 63% for 2D ultrasonography [ 6 , 8 ]. The detection rate for anomalies of the first trimester 3D VR ultrasound is 62.5% [ 20 ]. For second trimester (18–22 weeks’ gestation) 2D ultrasound the detection rate lies between 44.3 and 74.4% [ 40 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation